Orthopaedic knowledge update pediatrics 6 - Martus, Jeffrey E. (Wolters Kluwer ; American Academy of Orthopaedic Surgeons, 2022)
"Orthopaedic Knowledge Update®: Pediatrics 6 reflects the most recent clinical practice guidelines and appropriate use criteria, as well as the substantial number of high-quality studies in pediatric orthopaedics. This comprehensive multispecialty resource explores the latest advances in pediatric trauma, sports-related injuries, and upper and lower extremity conditions, with brand-new chapters on developmental biology, metabolism, high-energy injury and polytrauma, elbow trauma, knee trauma, and disaster response. Key study points are presented at the end of each chapter so you can quickly review important content. Recognized section editors and contributors bring fresh approaches and perspectives, with a focus on delivering a well-rounded update of this rapidly evolving subspecialty. This concentrated guide to new techniques, new approaches, and current controversies is ideal for anyone who treats pediatric musculoskeletal injuries"--